Intergrasi Sosial Tradisi Padugku terhadap Masyarakat Desa Sangele Kecamatan Pamona Puselemba - Kulyawan, Roy; Riandana, Taufik Eka (Jurnal Kreatif Online, 2020)
The Padungku tradition is used by the public to express gratitude for the harvest, and as a way to unite various ethnic communities. This study aims to determine the integration of the Padungku tradition in the immigrant community and to know the process of integration of the tradition, as well as the driving and inhibiting factors for the social integration of the tradition in Sangele Village, Pamona Pusalemba District. This research used desciptive qualitative approach. The data analysis process in this study used a phenomenological approach. The sampling technique was carried out using purposive sampling technique. The informants were village officials, traditional leaders, community leaders, religious leaders and the community. The results showed that the process of social integration of the Padungku tradition to the Sangele village community, Pamona Pusalemba sub-district occurred since the beginning of the entry of newcomers. All immigrant residents also participate in the celebration of the Padungku tradition, because of interaction in society, tolerance among communities and the similarities of their cultural elements. The inhibiting factor in the process of integrating the Padungku tradition is that there are some groups of people who want to mingle only with their fellow communities.